2006
DOI: 10.1001/archsurg.141.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Molgramostim (GM-CSF) Associated With Antibiotic Treatment in Nontraumatic Abdominal Sepsis

Abstract: The addition of molgramostim (recombinant human granulocyte-macrophage colony-stimulating factor) to antibiotic therapy for nontraumatic and generalized abdominal sepsis is effective and has a significant impact on length of hospitalization, direct medical costs, and mortality. Design: Randomized, double-blind, placebo-controlled clinical trial. Setting: Tertiary referral center. Patients: Fifty-eight patients with abdominal sepsis. Interventions: Patients were allocated to receive, in addition to ceftriaxone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 26 publications
1
30
1
Order By: Relevance
“…Among the selected trials, three trials were conducted in North America [40,44,45], two in Europe [43,48], two in Asia [39,46] and two in Australia [41,47]. Five trials were multicenter studies [37,38,40,42,48].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the selected trials, three trials were conducted in North America [40,44,45], two in Europe [43,48], two in Asia [39,46] and two in Australia [41,47]. Five trials were multicenter studies [37,38,40,42,48].…”
Section: Resultsmentioning
confidence: 99%
“…Randomized allocation sequence was adequately generated in six trials [41-43,46-48], for the other six trials it was judged to be unclear based on the available documents [37-40,44,45]. Allocation sequences concealment was adequately reported in six trials [41,43,44,46-48] and was judged to be unclear in the other six trials [37-40,42,45].…”
Section: Resultsmentioning
confidence: 99%
“…These trials have varied significantly in the clinical characteristics of the patients enrolled, the dose and duration of GM-CSF treatment, and the endpoints measured. Separately, they have demonstrated reduced evidence of leukocyte deactivation and more rapid resolution of sepsis (30), more rapid clinical improvement in abdominal sepsis (31), and improved leukocyte function and pulmonary gas exchange in patients with severe sepsis and respiratory dysfunction (32-33). Although the doses, site of administration, and duration of GM-CSF administration have varied, these studies together indicate that treatment with GM-CSF is well tolerated in patients with severe sepsis and suggest trends toward improvements in secondary endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic protocols with GM-CSF, G-CSF and IFNγ have been conducted in sepsis with the aims to stimulate innate immune function, improve myelopoiesis and limit lymphocyte apoptosis. Small clinical studies in ICU patients with sepsis or trauma showed no effect to decrease mortality but there was a beneficial effect on illness severity and rate of pathogen clearance [3842]. Interestingly, no study detected any adverse events.…”
Section: Monitoring Innate Immune Alterations In Sepsis and Related Tmentioning
confidence: 99%